Who will fight for AI in healthcare (Data Science Salon, 2020)
"Presented by Amy Daali, Chair at IEEE Engineering in Medicine & Biology Society. With recent advancements in artificial intelligence, the healthcare industry is primed to benefit significantly from Machine Learning and Deep Learning technologies. This talk will answer the burning question on who is going to fight for AI in healthcare? New concepts such as 'DIY healthcare' will be explored. We will discuss key important players who are going to lead the battle and drive AI adoption in 2020. Together, we will navigate the current Health Technology Landscape and uncover the different challenges that are preventing the implementation of AI. We will conclude the talk by exploring how we can improve collaboration between the Data Science and Medical community to speed up AI adoption in healthcare."--Resource description page